The effect of G0S2 on insulin sensitivity: A proteomic analysis in a G0S2-overexpressed high-fat diet mouse model - Wu, Dongming; Zhang, Zhenyuan; Sun, Wenxiu; Yan, Yong; Jing, Mengzhe; Ma, Shizhan (Frontiers in Endocrinology, 2023)
Background: Previous research has shown a tight relationship between the G0/G1 switch gene 2 (G0S2) and metabolic diseases such as non-alcoholic fatty liver disease (NAFLD) and obesity and diabetes, and insulin resistance has been shown as the major risk factor for both NAFLD and T2DM. However, the mechanisms underlying the relationship between G0S2 and insulin resistance remain incompletely understood. Our study aimed to confirm the effect of G0S2 on insulin resistance, and determine whether the insulin resistance in mice fed a high-fat diet (HFD) results from G0S2 elevation. Methods: In this study, we extracted livers from mice that consumed HFD and received tail vein injections of AD-G0S2/Ad-LacZ, and performed a proteomics analysis. Results: Proteomic analysis revealed that there was a total of 125 differentially expressed proteins (DEPs) (56 increased and 69 decreased proteins) among the identified 3583 proteins. Functional enrichment analysis revealed that four insulin signaling pathway-associated proteins were significantly upregulated and five insulin signaling pathway -associated proteins were significantly downregulated. Conclusion: These findings show that the DEPs, which were associated with insulin resistance, are generally consistent with enhanced insulin resistance in G0S2 overexpression mice. Collectively, this study demonstrates that G0S2 may be a potential target gene for the treatment of obesity, NAFLD, and diabetes.